2021
DOI: 10.3390/su132313146
|View full text |Cite
|
Sign up to set email alerts
|

Supply Chain Governance Mechanisms, Green Supply Chain Management, and Organizational Performance

Abstract: While firms understand that implementing green supply chain management (GSCM) is important, they seem uncertain about how to manage their green initiatives by looking beyond their own facilities. Building a green supply chain requires the participation of all partner firms across the supply chain. However, partner firms are different in size, situation, capabilities, and even industries. Thus, encouraging them to participate in green initiatives is difficult. Many small and medium enterprises (SMEs) hesitate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 82 publications
0
18
0
1
Order By: Relevance
“…When it comes to implementing eco-friendly sustainable logistics operations, four obstacles were found: consumer priorities, management complexity, network imbalance and uncertainty over new technical or legal developments as the four main hurdles (15). It has been shown that GL innovation may lower the environmental effect of logistics activities and boost company competitiveness and sustainability (16). Upstream supply chain measures can enforce environmental friendliness on logistics businesses, a downstream supply chain participant (17).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…When it comes to implementing eco-friendly sustainable logistics operations, four obstacles were found: consumer priorities, management complexity, network imbalance and uncertainty over new technical or legal developments as the four main hurdles (15). It has been shown that GL innovation may lower the environmental effect of logistics activities and boost company competitiveness and sustainability (16). Upstream supply chain measures can enforce environmental friendliness on logistics businesses, a downstream supply chain participant (17).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Their study showed that how choice of governance mechanism can affect the companies green supply chain management performance and competition. It showed that formal governance can affect process management (16). In 2021, research was conducted on south Asian countries using panel data estimation.…”
Section: Logistics and Sustainable Economymentioning
confidence: 99%
See 1 more Smart Citation
“…It has become difficult for organizations to achieve sustained innovation and competitive advantage internally. Therefore, some of the large organizations, like Xerox and Hitachi, had made collaborations outside the organizations to achieve sustained competitive advantage and innovation (Lee and Choi, 2021 ). Such collaborations may facilitate the KM or result out from the firm's pursuit to use new knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…Illustratively, Apple assessed the market potential of smart wearables, quickly focused on the development of smartwatches, and released it within 2 years, which captured 75.5% of the smartwatch market's share globally (Cai et al, 2019 ). On the other hand, attaining this kind of agility is not easy for most of the business organizations (Lee and Choi, 2021 ). However, it is necessary to understand how organizational agility contributes to the development of a new product.…”
Section: Introductionmentioning
confidence: 99%